Kinetic and thermodynamic parameters of the Li/Li+ couple in the room temperature ionic liquid N-butyl-N-methylpyrrolidinium bis(trifluoromethylsulfonyl) imide in the temperature range 298-318 K: a theoretical and experimental study using Pt and Ni electrodes. - Wibowo, R; Ward Jones, SE; Compton, R (2009)
The Li/Li+ couple is investigated in the room temperature ionic liquid N-butyl-N-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide, [C4mpyrr][NTf2], at a range of temperatures varying from 298 to 318 K.Experiments are conducted using both nickel and platinum microelectrodes. On nickel, a single stripping peak is observed for the stripping of bulk lithium that allowed thermodynamic and kinetic parameters to be extracted via computational simulation. At 298 K, the electrochemical rate constant (k0) ) 1.2 X 10-5 cms-1, the diffusion coefficient (D) ) 4.5 X 10-8 cm2 s-1, the formal potential (E(f)0 ) -3.26 V versus the Fc/Fc+ reference couple, and the transfer coefficient (alpha) = 0.63. On platinum, multiple stripping peaks are observed due to the stripping of Li-Pt alloys in addition to the stripping of bulk lithium. The ratio of the different stripping peaks is found to change with temperature, indicating that Li-Pt alloys are more thermodynamically stable than pure bulk lithium and platinum.